If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(2x + 1) + -3x = 8 Reorder the terms: y(1 + 2x) + -3x = 8 (1 * y + 2x * y) + -3x = 8 Reorder the terms: (2xy + 1y) + -3x = 8 (2xy + 1y) + -3x = 8 Reorder the terms: -3x + 2xy + 1y = 8 Solving -3x + 2xy + 1y = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -3x + 2xy + 1y + -1y = 8 + -1y Combine like terms: 1y + -1y = 0 -3x + 2xy + 0 = 8 + -1y -3x + 2xy = 8 + -1y Reorder the terms: -8 + -3x + 2xy + y = 8 + -1y + -8 + y Reorder the terms: -8 + -3x + 2xy + y = 8 + -8 + -1y + y Combine like terms: 8 + -8 = 0 -8 + -3x + 2xy + y = 0 + -1y + y -8 + -3x + 2xy + y = -1y + y Combine like terms: -1y + y = 0 -8 + -3x + 2xy + y = 0 The solution to this equation could not be determined.
| y-40-1(x-15)= | | 3x^2-30x=33 | | xsquared=2y | | 9b-6= | | 4/9x^2-1=0 | | 11+15v=7+13v | | 3(2m+5n)-4n= | | 6x^3+17x^2-28x=0 | | Y=x^4-81 | | -6+(-6)+4(-2)= | | 3x^3+22x^2-45x=0 | | 45*-5=x | | (u^2+3u-40)/(2u^2-14u+20) | | y-8(x-5)= | | (8x+5)(3x^2-11x-4)=0 | | -1by-1= | | 5t-1=-11 | | f(5)=x^2-x+2 | | 5x=2x+11 | | 64m^2-25n^2= | | 7/10+4=5 | | 180x^2-154x+30=0 | | (4x-9)(3x+8)= | | 4/5x1/2-2/8 | | 4/5x1/2 | | 0.67x+3=0.6 | | w(w-5)=36 | | 21x+3y=-18 | | x*10*x=495 | | x(10x)=495 | | (8x^3-4x^2+7x)-(7x^2+2x+5)= | | 3/8x=4/9 |